One judge to rule them all: single-member courts as an answer to delays in criminal trials - Alysandratos, Theodore; Kalliris, Konstantinos (SSRN, 2022)
This paper is a discussion of whether single-member judicial panels are an effective way of accelerating the delivery of criminal justice. We use a reform which introduced single-member courts in Greece, where delays in court proceedings are common according to the European Justice Scoreboard and the European Court of Human Rights. We use a novel dataset of 1468 drug trafficking cases tried between June 2012 and January 2014. We introduce a new measure of efficiency, the time to issue a decision, and we find that single-member panels are as efficient as three-member ones. We take advantage of a feature of the reform to control for several confounding factors and support a causal interpretation of our findings. We complement our analysis with data from the Ministry of Justice that show single-member panels have a higher clearance rate, and with a survey of 142 judges to guide our interpretation of the results
Gesehen am 05.05.2023
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments February 15, 2022 erstellt